Emoção e patriotismo nos jornais da independência (1821-1823) - Reis, Arthur Ferreira (2022)
This thesis as analyzedthe newspapers which have been printed in the Kingdom of Brazil during the years 1821, 1822 and 1823 in order to understand the themes and words which have circulated in them. To do so, we look not only at the print material, but also at the contexts in which it was published and the relationship it established with each other. Thus, through a perspectivethat seeks to relate these realities, we try to understand from the newspapers that circulated in the provinces of Rio de Janeiro, Bahia, Pernambuco, Pará and Maranhão how the independence process was reported and discussed in these different regions. To this end, we are combining traditional methods of interpreting text such as language context-driven reading and new analytical tools that have taken up space in the field known as the digital humanities. In this way, we associate the reading of the newspapers with the results of a software called Iramuteq.The study of the sources using this methodology has revealed that the periodicals tried to convince and persuade the public in favor of their political projects. For this, they used a patriotic and emotional language, in which terms such as “love”, “happiness” and “homeland” were essential.This discussion is in relation to the political changes and the crisis that was unfolding in the United Kingdom of Portugal, Brazil and Algarve. Amidst the disputes and disagreements that have arisen between the various political projects that have permeated the Bragantine monarchy, possibilities and expectations appeared and then they were explored, exhibited and materialized into political projects defended by the elites. In doing so, not only was the vocabulary changed to suit their interests, but also political identities were manipulated as a means of mobilizing the public.